Gambaran Keterlambatan Mencari Pengobatan ke Pelayanan Kesehatan pada Penderita Leptospirosis dan Faktor-faktor Terkait di Kota Semarang Description of Delayed to Health Care Seeking Treatment in Leptospirosis and its Related Factors in Semarang City - Reza Ayu Rizqi Meilani; Mateus Sakundarno Adi; Sri Yuliawati (Fakultas Kesehatan Masyarakat Universitas Diponegoro, 2016)
Delayed to health care seeking treatment in leptospirosis is still a problem in leptospirosis prevention activities in Indonesia. The problem is thought to be the cause of the high number of mortality due to leptospirosis. The objective of this study was to describe of delayed treatment in leptospirosis sufferer and its related factors in Semarang at 2014-2015. This study was descriptive study by using a cross-sectional design. The sampling technique used was proportional stratified random sampling. The samples of the study was 60 respondents, and taken randomly by simple random sampling. The result of the study showed that leptospirosis sufferer delayed the treatments with the number of 58.3%.